2018
DOI: 10.1001/jamainternmed.2018.2610
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between the Patient Protection and Affordable Care Act Medicaid Primary Care Payment Increase and Physician Participation in Medicaid

Abstract: Care Act (ACA) increased 2013 to 2014 Medicaid payment rates for qualifying primary care physicians (PCPs) and services to higher Medicare payment levels, with the goal of improving primary care access for Medicaid enrollees. OBJECTIVES To evaluate the payment increase policy and to assess whether it was associated with changes in Medicaid participation rates or Medicaid service volume among PCPs. DESIGN, SETTING, AND PARTICIPANTS This study used 2012 to 2015 IMS Health aggregated medical claims and encounter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 18 publications
3
38
0
Order By: Relevance
“…15 Existing studies on the impact of the ACA fee bump focus on Medicaid-only enrollees and have not found increases in PCPs’ participation in Medicaid, although 1 study found increases in appointment availability for Medicaid vs commercial enrollees during the fee bump. 16 , 17 , 18 , 19 These studies have not examined changes in beneficiary use associated with the fee bump, and those examining PCPs’ Medicaid participation exclude nurse practitioners (NPs) and physician assistants (PAs), who are increasingly providing primary care, especially in rural and low-income areas where Medicare beneficiaries are more likely to be dual. 20 , 21 NPs and PAs were eligible for the fee bump if working under the supervision of a physician.…”
Section: Introductionmentioning
confidence: 99%
“…15 Existing studies on the impact of the ACA fee bump focus on Medicaid-only enrollees and have not found increases in PCPs’ participation in Medicaid, although 1 study found increases in appointment availability for Medicaid vs commercial enrollees during the fee bump. 16 , 17 , 18 , 19 These studies have not examined changes in beneficiary use associated with the fee bump, and those examining PCPs’ Medicaid participation exclude nurse practitioners (NPs) and physician assistants (PAs), who are increasingly providing primary care, especially in rural and low-income areas where Medicare beneficiaries are more likely to be dual. 20 , 21 NPs and PAs were eligible for the fee bump if working under the supervision of a physician.…”
Section: Introductionmentioning
confidence: 99%
“…53 Other potential levers for improving the program may include alternative payment models that hold providers accountable for access; 24,26 changes in the supply, training, and mix of the health care workforce; or telemedicine. 45 Given the disparities observed in this study, a high priority should be placed on approaches with the potential to address differences in urban-rural access, as well as Medicaid-commercial disparities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies of the ACA's 2013/2014 primary care fee Bbump^-which resulted in an average increase in primary care payments of more than 70%-found no association with primary care providers' participation in Medicaid or Medicaid service volume. 45,46 While reimbursement may matter, physicians may be more responsive to efforts to simplify Medicaid's administrative processes and increase the speed of reimbursement. 47 Recent network adequacy regulations, which require Medicaid managed care plans in every state to set standards for specialty care access, including limits on wait times and distance traveled, may also narrow existing disparities in access.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Between 2013 and 2015, full-time equivalent physicians participating in Medi-Cal increased by only 9% while Medi-Cal beneficiaries increased by 60%, presenting challenges for enrollees seeking medical care. 9 Although studies of appointment availability from other states report that expansion of the Medicaid program has led to more, not less, access to PCCs, [10][11][12] payment increases have also been reported to have little effect on Medicaid clinician participation rates across states 13 despite increased 2013-2014 PCC reimbursement rates.…”
mentioning
confidence: 99%